The worst of all possible worlds - White, Alex (Novelist) (The Salvagers, 2020)
"The rag-tag crew of the Capricious is hunting down rogue AI, ancient colony ships, and the biggest treasure the universe has ever seen in the final book of this pulse-pounding space adventure series for fans of Firefly and The Expanse. The crew of the Capricious seems to leave a trail of devastation wherever they go. But with powerful enemies in pursuit and family and friends under attack planetside, there's no time to worry about all that. Ensnared by the legend of Origin, humanity's birthplace, and a long-dead form of magic, the Capricious takes off on a journey to find the first colony ship...and magic that could bring down gods"--